Mortality in admitted diabetic patients in the Hospital of Puyo, Pastaza province, Ecuador - Mayra Alejandra Bayas Aranda; Johnnatan Gustavo Rivera Almeida; Edison Ramiro Samaniego Layedra; Patricia del Rocío Asadobay Escobar (Medisur)
Foundation: Diabetes mellitus is a chronic disease which is characterized by a sustained increase in blood glucose levels. It is described as one of the main causes of morbidity and mortality worldwide, as well as responsable for different degrees of disability and a great impact on health-related quality of life. Objective: to characterize mortality in admitted diabetic patients in the General Hospital of Puyo. Methods: a descriptive study, carried out in the Hospital of Puyo, Pastaza province, Ecuador, during 2016 and 2017, with 168 patients, of which 20 were deceased. The medical records of each of the cases included in the study were reviewed. The variables were: sex, age, glycemic control, cause of admission, time of disease evolution and duration of admission. Results: in the deceased, the average age was 72 years. There was a predominance of female patients (65.0%), with time of evolution of the disease of more than three years (90.0%), and with an inadequate glycemic control (70.0%). Inter current diseases were the main causes of income and deaths (75.0%). Conclusion: diabetic patients who died had inter current diseases as the most frequent cause of admission, older than 70 years most of them, time of evolution of disease greater than three years and presence of an inadequate metabolic control.